Patient-led Remote IntraCapillary pharmacoKinetic Sampling (fingerPRICKS) for Therapeutic Drug Monitoring in patients with Inflammatory Bowel Disease. (21st July 2021) - Chee, Desmond; Nice, Rachel; Hamilton, Ben; Jones, Edward; Hawkins, Sarah; Redstone, Clare; Cairnes, Vida; Pohl, Keith; Chanchlani, Neil; Lin, Simeng; Kennedy, Nicholas A; Ahmad, Tariq; et al.
Abstract: Background and Aims: Because of COVID-19 public health restrictions, telemedicine has replaced conventional outpatient follow up for most patients with chronic immune-mediated inflammatory disorders treated with biologic drugs. Innovative solutions to facilitate remote therapeutic drug monitoring are therefore required. Low-volume intracapillary blood sampling can be undertaken by patients at home and samples returned by post to central laboratories. We sought to report the effect of the COVID-19 pandemic on requests for therapeutic drug monitoring and the equivalence, acceptability and effectiveness of low volume Patient-led Remote IntraCapillary pharmacoKinetic Sampling [fingerPRICKS] compared to conventional venepuncture. Methods: We undertook a cross-sectional blood sampling methods comparison study and compared sample types using linear regression models. Drug and antidrug antibody levels were measured using standard ELISAs. Acceptability was assessed using a purpose-designed questionnaire. Results: Therapeutic drug monitoring requests for adalimumab (96.5 [70.5–106] per week to 52 [33.5–57.0], p < 0.001) but not infliximab (184.5 [161.2–214.2] to 161 [135–197.5], p = 0.34) reduced during the first UK stay-at-home lockdown compared with the preceding 6 months. Fingerprick sampling was equivalent to conventional venepuncture for adalimumab, infliximab, vedolizumab and ustekinumab drug, and anti-adalimumab and anti-infliximab antibody levels. The median [interquartile range] volume of serum obtained using intracapillary sampling was 195 µL [130–210]. More than 87% [90/103] of patients agreed that intracapillary testing was easy and 69% [71/103] preferred it to conventional venepuncture. In routine care, 75.3% [58/77] of patients returned two blood samples within 14 days to permit remote assessment of biologic therapeutic drug monitoring. Conclusions: Therapeutic drug monitoring can be undertaken using patient-led remote intracapillary blood sampling and has the potential to be a key adjunct to telemedicine in patients with immune-mediated inflammatory diseases.